Wykorzystanie narzędzi graficznych do budowania zrównoważonych portfeli nowych produktów - Golej, Robert (Using Graphically Methods to Build Balanced Portfolios of the New Products, 2005)
There are two ways for a business to succeed at new products: doing projects right, and doing the right projects. Portfolio management focuses on the second route, namely on doing the right projects. The portfolio management is characterized by uncertain and changing information, dynamic opportunities, multiple goals and strategic considerations, interdependence among projects, and multiple decision-makers and locations. The obtainment the balance of portfolio NPD is one of main aims of portfolio management. The graphic forms are the basic tool of building of balance portfolio.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 110-121